Advances in advertising research (Vol. III) : Current insights and future trends - Langner, Tobias; Okazaki, Shintaro; Eisend, Martin (European Advertising Academy, 2012)
Advances in Advertising Research are published by the European Advertising Academy (EAA). This volume is a compilation of research presented at the 10th International Conference on Research in Advertising (ICORIA) which was held in Berlin (Germany) in June 2011. In the face of an ever increasing number of products and services, as well as an increasingly cluttered media environment, advertising research is confronted with multiple challenges. Against this background, the book provides international state-of-the-art research with 32 articles by renowned scholars from the worldwide ICORIA network.